The Effectiveness of Digital Literacy in Improving Community Skills in the Tanjung Kasau Plantation Village - Ismayadi; Zulfan; Putra Armidin, Ranu; Marpaung, T.J.; Satria Lubis, Andrew; Marpaung, J.L.; Gunaika, Raka; Hayatunnufus; Siringoringo, Y.B.; Azhari; Munzaimah (Talenta Publisher, 2023)
Low technological literacy and an ecosystem for developing innovation and creation that is not built at the village level are one of the reasons why the village is not developing. The use of information technology can be a medium that connects the community and village government. The village government can utilize information technology to deliver services related to governance and village development as well as fostering and developing community empowerment. This service will focus on increasing digital literacy to support communities that are resilient in digitizing MSME activities.